Penerapan Laporan Keuangan Berkelanjutan berdasarkan PSPK 1 dan PSPK 2 di Indonesia - Dita Hikmawaty Oktavia Ningrum; Aliya Dimarizkya; Natasha Elisabeth Manuputty; Aisya Sheilla Farina Nadia; Daryanto Hesti Wibowo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study discusses the implementation of PSPK 1 and PSPK 2 in sustainability reporting in Indonesia. The Financial Services Authority (OJK) requires public companies in Indonesia to prepare sustainability reports as a form of accountability for environmental, social, and governance (ESG) aspects. PSPK 1 and PSPK 2 serve as the standard basis for assurance services on these reports. However, the quality, consistency, and reliability of ESG data remain major issues. This study examines this phenomenon from the perspective of accounting theory and the accounting challenges in measuring and verifying non-financial information in the transition era to a low-carbon economy. The results of the literature and theoretical studies indicate that sustainability reporting must be regulated in such a way that it is not merely an administrative compliance requirement because it is often considered less relevant to company strategy. Furthermore, there is a need to emphasize the importance of governance structures and sustainability report audit standards (such as PSPK 1 and PSPK 2) to encourage truly accountable reporting that has a real impact on the economy, society, and environment.